Comportamiento biológico del carcinoma oral de células escamosas : estudio inmunohistoquimico de cd44 y aldh1a - Cortegoso, Aurita Veronica Beovide (2020)
The present study comprise a period of 4 to 5 years of work in a doctoral project where the topic of oral cancer was approached from different lines of study. In the first article, an update was made on the biological behavior of oral squamous cell carcinoma, describing the importance of this aggressive behavior and its implication in tumor invasion, dissemination and the production of distant metastases, characteristics that describe the Oral cancer. In the second article, a review was made on the importance of cáncer stem cells and field cancerization in oral cancer. This subpopulation of cells would be the conductors of tumorigenesis and tumor growth and responsible for directing the processes that lead to resistance to therapies and the production of distant metastases. The third research article, where an epithelial cell identification work was performed in oral squamous cell carcinomas and epithelial dysplasia by immunohistochemistry with the CD44 and ALDH1A biomarkers. Where the association of ALDH1A positivity in the survival of patients was observed, as a possible prognostic marker and since it was not possible to identify an association of ALDH1A positivity with tumor cells and adjacent non-tumor tissue, it is shown to be of little value for the pathogenesis of head and neck cancer.